2021
DOI: 10.1038/s41598-021-85100-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa PA80 is a cystic fibrosis isolate deficient in RhlRI quorum sensing

Abstract: Pseudomonas aeruginosa uses quorum sensing (QS) to modulate the expression of several virulence factors that enable it to establish severe infections. The QS system in P. aeruginosa is complex, intricate and is dominated by two main N-acyl-homoserine lactone circuits, LasRI and RhlRI. These two QS systems work in a hierarchical fashion with LasRI at the top, directly regulating RhlRI. Together these QS circuits regulate several virulence associated genes, metabolites, and enzymes in P. aeruginosa. Paradoxicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 121 publications
(137 reference statements)
1
7
0
Order By: Relevance
“…In contrast, we found evidence for QS regulon modulation in the Rhl mutants. These mutants arose at a much lower frequency than the Las mutants, similar to previous studies ( 54 , 55 ). Both the phenotypic profiles and gene expression analyses revealed that there is no complete loss of QS function, but rather a change in the expression of the QS-regulated trait profile.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, we found evidence for QS regulon modulation in the Rhl mutants. These mutants arose at a much lower frequency than the Las mutants, similar to previous studies ( 54 , 55 ). Both the phenotypic profiles and gene expression analyses revealed that there is no complete loss of QS function, but rather a change in the expression of the QS-regulated trait profile.…”
Section: Discussionsupporting
confidence: 91%
“…These results support the recent findings of Luján et al, who demonstrated that pqsR-regulated QS system is retained in the presence of competing taxa and mucin, likely due to the fitness benefits of retaining the redox agent pyocyanin, an effective anti-competitor toxin 18 . Mutations in QS transcriptional regulators pqsR and vqsM are commonly observed during in vitro evolution of P. aeruginosa [17][18][19]38,48,49 , but mutations in these genes are rarely observed in chronic adapted strains isolated from CF sputum 5,50 . Our results suggest that mutations within these QS transcriptional regulators are dependent upon the interaction between the community composition and the physical environment, whereby intense competition coupled with the presence of mucin provide strong selection for the retention of these QS transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, more and more studies have found that the rhl system occupies a more dominant position. The rhl system is directly related to the drug resistance of P. aeruginosa , and in the case of poor nutritional conditions, structural level changes, and can regulate the expression of related genes of the las system [ 27 ]. In addition, lasR deletion mutants are prevalent in patients with chronic P. aeruginosa infections, and these mutants have stronger rhl system activity than the wild strains [ 28 ].…”
Section: Discussionmentioning
confidence: 99%